The Effectiveness of Aromatherapy Essential Oil Aroma Orange in Reducing Pain Scale 24 Hours Post Cesarean Section - Herlyssa Herlyssa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Aromatherapy can help with post-Sectio caesaria (SC) pain. Aromatherapy orange is a sort of aromatherapy that can be used to alleviate pain and anxiety because it includes linalool, which helps to balance the nervous system and has a relaxing impact on those who inhale it. The purpose of this study is to investigate the efficacy of Aromatherapy Essential Oil Aroma Orange in lowering pain scale 24 hours after SC. The study's design was quasi-experimental, comprising a pre- and post-test with a control group. The research sample consisted of 74 people who were randomly assigned to one of two groups (treatment or control). The results showed that after receiving essential oil aromatherapy, the pain scale in the treatment group decreased from 4.141.669 to 2.591.334 (P value=0.000). Meanwhile, in the control group, the ratio was 2.860.419 to 2.780.479 (P=0.373). There is a difference in pain scale 24 hours after SC in moms who had a longer procedure (P-value=0.008). This indicates that essential oil aromatherapy with an orange scent can help alleviate discomfort. To be administered as a treatment to alleviate post-SC pain 24 hours after surgery.